Analiza wybranych wskaZników wydolnosci tlenowej i beztlenowej u zapasników w okresie przygotowawczym - Jastrzebski, Z.; Laskowski, R. (Medycyna sportowa, 2000)
The aim of this study was to analyse selected indices of anaerobic and aerobic capacities of wrestlers in the preparatory period of the training cycle. A group of 12 cadet wrestlers participated in the study. The PWC170 test was used to determine the aerobic capacity and the 30 s Wingate test - to determine the anaerobic capacity. A "Monark" cycle ergometer was used in both tests. The mechanical parameters (work and maximum power outputs, time to attain and to maintain maximum power, power drop index) were recorded with the use of MCE V. 2.0 software and analysed using the Student's t-test. The results indicated a significant improvement in the anaerobic capacity and a stabilisation of the aerobic capacity of wrestlers in the preparatory period of the training cycle.